2014
DOI: 10.1016/j.regsciurbeco.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foreclosures on nearby housing prices: Supply or dis-amenity?

Abstract: a b s t r a c tA number of studies have measured negative price effects of foreclosed residential properties on nearby property sales. However, only one other study addresses which mechanism is responsible for these effects. I measure separate effects for different types of foreclosed properties and use these estimates to decompose the effects of foreclosures on nearby home prices into a component that is due to additional available housing supply and a component that is due to dis-amenity stemming from deferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 11 publications
2
43
0
Order By: Relevance
“…Discounted recent foreclosures can lower the perceived and appraised value of neighboring homes. Most of the results clustered around a 1 percent lower sale price for each nearby foreclosure (Immergluck and Smith, 2006;Schuetz, Been, and Ellen, 2008;Harding, Rosenblatt, and Yao, 2009;Leonard and Murdoch, 2009;Rogers and Winter, 2009;Rogers, 2010;Campbell, Giglio, and Pathak, 2011;Groves and Rogers, 2011;Hartley, 2014). One study by Lin, Rosenblatt, and Yao (2009) estimated that each foreclosure liquidation can depress shortrun property values of homes within a half mile as much as 8.7 percent in down markets and 5 percent in up markets.…”
Section: Literaturementioning
confidence: 99%
“…Discounted recent foreclosures can lower the perceived and appraised value of neighboring homes. Most of the results clustered around a 1 percent lower sale price for each nearby foreclosure (Immergluck and Smith, 2006;Schuetz, Been, and Ellen, 2008;Harding, Rosenblatt, and Yao, 2009;Leonard and Murdoch, 2009;Rogers and Winter, 2009;Rogers, 2010;Campbell, Giglio, and Pathak, 2011;Groves and Rogers, 2011;Hartley, 2014). One study by Lin, Rosenblatt, and Yao (2009) estimated that each foreclosure liquidation can depress shortrun property values of homes within a half mile as much as 8.7 percent in down markets and 5 percent in up markets.…”
Section: Literaturementioning
confidence: 99%
“…These authors find that both mechanisms are at work, and their effects are strongly associated with the distances to nearby houses. Hartley (2014) examines the influence of foreclosures on nearby housing prices and finds that the decline in neighborhood home prices is influenced only by increases in nearby housing supply. Calomiris, Longhofer, and Miles (2013) identify a bidirectional relationship between housing prices and foreclosures in state housing markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This statement showed that they are areas overlooked and not addressed properly particularly on methods to measure the quality level of housing. Previous research conducted by other researchers such as Khoiry, Tawil, Hamzah, Ani, & Sood, (2012), Hillebrand & Kikuchi, (2015), and Hartley, (2014) showed degree of efforts to identify factors of characteristic house qualities, but their research produced little empirical and theoretical basis in identifying quality level off for each specific characteristics for houses. These studies conducted analysed the factors primarily, and have a minimal amount of measuring and ranking the weightings of the characteristics qualities.…”
Section: Measurement For Characteristics Of Housingmentioning
confidence: 99%